FACTORS AFFECTING EXCLUSIVE BREAST FEEDING AMONG POSTNATAL MOTHERS IN GOMBE HOSPITAL, BUTAMBALA DISTRICT. A CROSS-SECTIONAL STUDY. - Gladys Uwizera; Donatus Kimera (Student's Journal of Health Research, 2023)
Background:   The study explored factors affecting exclusive breastfeeding among postnatal mothers in Gombe Hospital, Butambala District. The objectives that guided the study were: to identify socio-economic factors affecting exclusive breastfeeding practices, challenges faced by breastfeeding mothers, and mothers' knowledge of exclusive breastfeeding.   Methodology:   This study was quantitative; 40 participants were selected using convenience sampling.  The study was carried out in Gombe Hospital's young child clinic in January 2021. A structured questionnaire was used to collect data. Data were analyzed using SPSS version 20. Results: More than half of the mothers did not get help from staff on breastfeeding (72.5%), and 67.5% did not receive any help on positioning and attaching their babies to the breast. Some of the barriers found included the widely-held perception that infants needed water and formula to supplement, concern that breast milk alone does not satisfy the infant, inadequate infant feeding education and support by the health system, and the lack of community-based postnatal support and family influence.   Conclusion:   Midwives and health workers need to spend more time supporting and educating women about breastfeeding.    Recommendations:   There is a need for more training, follow-up, and research.